PENDAMPINGAN PEMBUATAN MIE DAN BISKUIT DARI TEPUNG SAYURAN PADA KELOMPOK IBU-IBU PETANI DI DESA SINDON NGEMPLAK BOYOLALI - Rusdin Rauf; - Muhtadi; Kun Harismah; - Saifuddin (Universitas Muhammadiyah Semarang, 2015)
The development of a variety of products processed from starchy vegetables needed to be trained and applied for the farmers of vegetables to help cope with the price of vegetables was very cheap and increased its economic value. This activity aimed to develop products processed from starchy vegetables in the village of Sindon-Ngemplak-Boyolali, which was expected to increase economicvalue, both in terms of revenues, new business development and the welfare of farmers. The partner of community development activities were ibu-ibu PKK , pengajian Aisyah and kelompok wanita tani (KWT)